2019
DOI: 10.3389/fneur.2019.00159
|View full text |Cite
|
Sign up to set email alerts
|

Improving Prehospital Stroke Services in Rural and Underserved Settings With Mobile Stroke Units

Abstract: In acute stroke management, time is brain, as narrow therapeutic windows for both intravenous thrombolysis and mechanical thrombectomy depend on expedient and specialized treatment. In rural settings, patients are often far from specialized treatment centers. Concurrently, financial constraints, cutting of services and understaffing of specialists for many rural hospitals have resulted in many patients being underserved. Mobile Stroke Units (MSU) provide a valuable prehospital resource to rural and remote sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 138 publications
2
28
0
Order By: Relevance
“…Other potential solutions include the use of mobile stroke units, prehospital triage, telemedicine for decision support, and flying intervention teams. [29][30][31][32][33][34][35][36] Direct transportation to intervention centers may be preferable to interhospital transfers, which can be associated with delays in treatment and worse outcomes. 23,[37][38][39] The designation of additional endovascular centers in underserved areas may be part of the solution, although it may be challenging to maintain a roster of staff and neurocritical care services in such areas, and one Korean study found that outcomes were worse at small-volume compared to large-volume sites.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential solutions include the use of mobile stroke units, prehospital triage, telemedicine for decision support, and flying intervention teams. [29][30][31][32][33][34][35][36] Direct transportation to intervention centers may be preferable to interhospital transfers, which can be associated with delays in treatment and worse outcomes. 23,[37][38][39] The designation of additional endovascular centers in underserved areas may be part of the solution, although it may be challenging to maintain a roster of staff and neurocritical care services in such areas, and one Korean study found that outcomes were worse at small-volume compared to large-volume sites.…”
Section: Discussionmentioning
confidence: 99%
“…Sites such as Lucas County serves a population of 433,689 (33); New Jersey model serves a modest population of 460,000 (34); and the Cleveland model serves a population of 390,000 (35). In Germany, there is exploration on the deployment of MSU in rural areas (16). In Edmonton, Canada, there is extension of the operating radius as far as 250 km from base (12).…”
Section: Discussionmentioning
confidence: 99%
“…There may be a need to allocate resources equitably from inner Sydney to outer Sydney while planning the location of MSU hub. This is an issue that is not unique to Australia but is also relevant in Europe (16) and Canada (12). In London, this had been addressed by reducing the number of hospitals providing thrombolysis service (24, 39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, proper early diagnosis and management is very important. As the reason above, pre-hospital stroke service is one of major concerns of treatment, includes emergency medical services(EMS) and pre-stroke education 13,18) . Distance and travel time to the nearest stroke center is a crucial issue for time-sensitive stroke treatment 5,13) .…”
Section: Introductionmentioning
confidence: 99%